Post-ultimate strength behaviour and collapse severity of ship hull girder under extreme wave load by an analytical method. (1st February 2022) - Xu, Weijun; Zhou, Xueqian; Li, Chenfeng; Ren, Huilong
ABSTRACT: When the external load exceeds the ultimate strength of hull girder, the load-carrying capacity is not completely lost due to the supporting and constraint between structure members. It is also determined by the post-ultimate strength behaviour, and the collapse severity needs to be studied to evaluate the consequence of collapse. An analytic approach is presented in this paper to analyse the factors influencing the collapse severity of hull girder under extreme wave load. The equations of motion of hull girder are derived for an external moment unloading in different ranges of the generalised moment-curvature relationship so as to predict the corresponding final severity of collapse. The severity is also analysed from the energy point of view to investigate the influence of the capacity drop on the severity. The complete post-ultimate strength behaviour of hull girder revealed in this study provides a reference for structure safety design of ship hull girders.